A Comparative Study of Error Analysis in Writing Narrative Texts Made by Junior, Senior and University Students - Kurniawan, Dwi Agung (2016)
This research points out the errors analysis in students' writing and it is aimed to decsribe the types of errors found in the students' writing result made by Junior, Senior, and University students, to know the frequencies of each type of errors found in the students' writing result made by Junior, Senior, and University Students, to explain the similarities and differences types of errors found in the students' writing result made by Junior, Senior, and University students, and to investigate the causes of errors found in the students' writing result made by Junior, Senior, and University students. There are three types of errors namely lexical error (22,46%), syntactical error (199,41%), and discourse error (100,37%). These types of errors have 13 categories of errors; 1) spelling; 2) false friend; 3) to be; 4) bound morpheme s/es; 5) verb tense; 6) articles (a,an,the); 7) preposition; 8) to infinitive; 9) modal auxiliary; 10) passive voice; 11) cohesion; 12) coherence; and 13) generic structure. There are eighteen error cases. The researcher found junior students made more errors than senior and university students, there are 91 errors sentences in junior students, whereas senior students have 43 erroneous sentences and university students have 35 erroneous sentences. The similarities of errors found in junior, senior and university students are: Omission of Bound Morpheme's/es' as the Plural Marker, Using Verb 1 for Past Event, Using Incorrect Verb 2, False Friend, Omission Errors in the Form of Preposition, Using Verb 1 after to Infinitive, Using Verb 1 after Modal Auxiliary, and Using Passive Voice Form Incorrectly. While, the differences errors found in junior, senior and university students are: The Use of Copula 'Be' Present Tense for Past Event in Junior Students, It does not find in Senior and University students' composition. The errors such as additional 'Be' for Past Event and Omission "Be" for past event that found in Junior and Senior students, but it does not include in university students' composition. The researcher found error. It is omission Errors in the Form of the Article (a, an, the) in Junior Students but It does not include in Senior and University's composition. There are four causes that lead students to errors, they are overgeneralization, incomplete application of rules, false concept hypothesized, and ignorance of rule restrictions. For this case, ignorance of rule restrictions is the most highest cause of error that occured in the students' writing with the percentage 114,74%. The error occured because the students fail to apply the rule of grammar in target language. Keywords: comparative, error analysis, interlanguage, grammar, writing.